Optimizing Educational Resources: A Paradigm for the Pursuit of Educational Productivity - James L. Phelps (Educational Considerations, 2008)
The advantage and perhaps the major motivation for using “seat-of-the-pants” decision making is that it obscures the assumptions made in arriving at a decision. If no one knows the assumptions upon which you based your decisions, then even though they may be uneasy with the decision they will have a difficult time criticizing your assumptions or decisions.
Keywords: Optimization; modeling; assumptions; paradigm; productivity; pursuit; regression analysis